Synthesis of Heat Exchangers Network (HEN) by Revisiting the Method Based on 2nd Law of Thermodynamics - Hoo, Shean Chuan (Universiti Teknologi PETRONAS, 2009)
As the project title implies, this project is basically about synthesizing an optimum heat exchanger network (HEN) by using a new approach which revisits second law of thermodynamics. This paper is started with introduction which gives an overview of project background, problem statement, objective, and scope ofproject. Then, literature review gives clearly about the theory of the project. The following section touches on methodology of the project. Algorithm of HEN has been displayed in this section. This project requires using simulation tools, such as HYSYS to find out the relationship between total exergy lost and hot stream outlet temperature. Formulation has been performed to obtain generic function equations for Cp, Hf, Sf, Hfg, Sfg. In the formulation process, Graph Software is used to choose the best fit trends for all these values with respect to their temperatures. Generic function equations are then used in the calculation of energy balance and exergy lost. All calculations are computed in a template in Microsoft Excel. T hot out and Cp coid out are considered as manipulated variables to decide the lowest exergy lost of the HEN. To solve for the minimum exergy lost of HEN more conveniently, "solver" in Microsoft Excel is used. Finally, the project is concluded in the last section. Recommendations on procedures are also stated to improve the method. Future works are including the transformation of algorithm into GAMS or other mathematical programming tools.